Pengembangan Laboratorium Virtual pada Materi Penanaman dan Pewarnaan Bakteri di SMA: Development of Virtual Laboratory on Bacteria Planting and Staining Materials in Senior High Schools - Sugiarti Sugiarti; M. Haris Effendi Hsb; Damris Muhammad (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2021)
The material for culturing and coloring bacteria is abstract, requiring other alternatives to understand the material through a practicum in a virtual laboratory. This development research aims to produce virtual laboratory media for high school students. The media development was carried out using the ADDIE model. Media and material experts' and product validation obtained results in a very good category. The feasibility of this virtual laboratory media was practically seen through the results of the teacher's response which is in the excellent category, and the analysis of the perception of small group students is in a good category. Trials for large groups of students were performed in the two classes of MIA. The obtained result was in an excellent category, with Choen's Kappa index of 0.47 (significant 0.00), indicating a fairly strong and significant agreement on the students' responses in both classes regarding the feasibility of the developed virtual laboratory media. It can be concluded that the virtual laboratory media on culturing and coloring bacteria is feasible to be used in schools as an alternative to practicum learning media.